PROSEDUR PELAPORAN IURAN UPAH TENAGA KERJA PADA PROGRAM JAMINAN SOSIAL TENAGA KERJA DI BPJS KETENAGAKERJAAN CABANG MEDAN BARAT - Fathan Ariq; Nuri Aslami (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to analyze the procedures for reporting labor wage contributions and elements of internal control on labor wage contributions so that the company's goals can be achieved. This type of research is descriptive qualitative research, using primary data and secondary data. Data collection is carried out through observation, interviews, and documentation. The data analysis used in this study is descriptive and uses relevant, accurate, and timely variables. The results showed that: a) BPJS Employment of West Medan Branch Office mentioned cash or cash receipts from its business income by reporting labor wage contributions. b) The reporting of labor wage contributions carried out by the BPJS Employment of West Medan Branch Office is good. BPJS Employment of West Medan Branch Office can divide the contribution report function into four functions, namely the administrative function, the financial function, the technology function, and information, and the marketing function. c) BPJS Employment of West Medan Branch Office carries out all incoming cash receipts, documents, or forms prepared based on the NPP and all contribution receipts either through current accounts or companies are directly deposited directly to the bank every day.